Diagnosis of discoid lupus erythematosus in a dog: Case report - Guilherme, Andrea Regina Cavazotto; Luppi, Marta Maria Círchia Pinto (Pubvet, 2024)
In veterinary medicine one of the biggest challenges of the small clinic are the rare autoimmune diseases, especially on dermatology care, due to their complexity and lack of response to conventional skin treatments. Lupus erythematosus is one of these diseases that, in addition to affecting humans, is often diagnosed in dogs, and among its various classifications are systemic lupus erythematosus and discoid lupus erythematosus, which some authors believe to be a benign variation of the systemic lupus. The present study aims to report the case of a 9-year-old mixed-breed dog, rescued and kept in a veterinary clinic since its adoption as a puppy. In recent years, he has presented several dermatological manifestations, being seen by several clinicians with different empirical treatments without success in the therapeutic responses, then being referred to a dermatology specialist in search of a diagnosis. In this phase, the clinical signs were apathy, weight loss, facial (especially periocular) erythematous, ulcerated, and crusted lesions, moderate pruritus and loss of cobblestone architecture to the nasal planum. After screening for the underlying cause with cytological examination, there were signs for three differential diagnoses: lupus, ischemic dermatitis and dermatomyositis, requiring a biopsy for histopathological examination to define the cause. The diagnosis was then obtained as lymphoplasmacytic lichenoid dermatitis associated with edema and apoptosis of keratinocytes, a pattern compatible with discoid lupus erythematosus, demonstrating that the assertive choice of diagnostic methods was fundamental in implementing the correct treatment and obtaining the remission of the disease.
Keywords: Lupus; autoimmune disease; dermatology; histopathology